2019
DOI: 10.1111/cobi.13310
|View full text |Cite
|
Sign up to set email alerts
|

Public views about editing genes in wildlife for conservation

Abstract: Developments in CRISPR‐based gene‐editing technologies have generated a growing number of proposals to edit genes in wildlife to meet conservation goals. As these proposals have attracted greater attention, controversies have emerged among scientists and stakeholder groups over potential consequences and ethical implications of gene editing. Responsible governance cannot occur without consulting broader publics, yet little effort has been made to systematically assess public understandings and beliefs in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 41 publications
1
28
1
1
Order By: Relevance
“…Less is known about the public's views of gene editing for non-human applications, such as for farming and agriculture. One study found that most U.S. adults believed gene editing for wildlife conservation was more risky, citing that the technology may be misused by those who have bad intentions [Kohl et al, 2019].…”
Section: Gene Editing Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Less is known about the public's views of gene editing for non-human applications, such as for farming and agriculture. One study found that most U.S. adults believed gene editing for wildlife conservation was more risky, citing that the technology may be misused by those who have bad intentions [Kohl et al, 2019].…”
Section: Gene Editing Technologymentioning
confidence: 99%
“…Religiosity, which we define as the level of devotion one has to their religion, may influence attitudes toward science topics; for example, individuals may believe that gene editing is messing with God's creation [Walker and Malson, 2020], and subsequently may have negative attitudes toward science in general. Similarly, political ideology may influence science attitudes, where those who are more conservative may have more negative views toward science topics [Kohl et al, 2019;Newman, Nisbet and Nisbet, 2018].…”
Section: Role Of Value Predispositionsmentioning
confidence: 99%
“…Building upon the limited quantitative studies to date that explore public attitudes towards genetic tools for conservation (Kohl et al 2019;MacDonald et al 2020) and the wider use for pest control for agricultural benefits (Jones et al 2019), our study used content analysis to gain insight into New Zealanders' perceptions of novel technologies for conservation. Eleven focus groups were conducted to explore three questions with regard to gene drive and two other forms of novel technologies for comparative purposes: the trojan female technique (Dowling et al 2015) and a pest-specific toxin (Campbell et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Pew Research Center also provides survey evidence from 2018 that 70% of U.S. adults viewed genetic engineering of mosquitoes for disease control as “an appropriate use of technology,” while 29% said it is “taking technology too far” ( 21 ). Kohl et al ( 22 ) investigate U.S. public attitudes toward the use of gene-editing tools, including in gene drives, in wildlife conservation and find that majorities perceive both risks and benefits of using these technologies in conservation. In terms of actual proposed releases of engineered insects, the Florida Keys Mosquito Control District conducted a nonbinding referendum in 2016 among residents of Monroe County, Florida, as part of a proposed trial release of a genetically engineered, nondrive Aedes aegypti mosquito developed by the company Oxitec.…”
Section: Introductionmentioning
confidence: 99%